Sense-making in the time of COVID-19: a study on the information needs of patients at the moment of confirmation - Abad, Einor John Godfrey L.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2022)
With the emergence of a global pandemic, this study aimed to find out how patients made sense of their situation upon finding out that they were positive for Covid-19. This study is heavily influenced by the sense-making model of Brenda Dervin, which divides the sense-making process of an individual into three main. components: the situation, Gap, and Use. Through these three parts, the study was able to find out the information needs and seeking strategies of Covid-19 patients.

This study made use of descriptive qualitative research design and collected data from respondents through semi-structured, open-ended, and in-depth interviews, The respondents of the study were previous Covid – 19 patients who were of legal age and have since recovered from the disease. To analyze their data, the study made use of a thematic analysis, which highlighted the main concepts that were collected from the interviews.

The results of the study show that the individual situations of the respondents play a key role in their information needs, and thus their way of seeking information. Respondents have varied concerns, questions, or gaps, depending on the situation that they were facing Covid- 19 patients are finally able to make sense of their experience one they have find useful information that has helped them in answering the concerns and questions that they initially had in mind.
Thesis
Keywords: Information behavior; COVID-19 (Disease) -- Patients